Association between family cancer history and risk of pancreatic cancer. (December 2016) - Schulte, Annaka; Pandeya, Nirmala; Fawcett, Jonathan; Fritschi, Lin; Klein, Kerenaftali; Risch, Harvey A.; Webb, Penelope M.; Whiteman, David C.; Neale, Rachel E.
Highlights: An association exists between family history of melanoma and pancreatic cancer. Family history of pancreatic cancer is a risk for the disease. No association was observed between family history of other cancers and pancreatic cancer within the Queensland Pancreatic Cancer Study (QPCS). Abstract: Purpose: Family history of pancreatic adenocarcinoma is an established risk factor for the disease. However, associations of pancreatic cancer with other familial cancers are less clear. We analyzed data from the Queensland Pancreatic Cancer Study (QPCS), an Australian population-based case-control study, to investigate associations between family history of various cancer types and risk of pancreatic cancer. Materials and methods: Our study included 591 pancreatic cancer patients and 646 controls, all of whom self-reported the histories of cancer in their first-degree relatives. We used logistic regression to estimate adjusted odds ratios (ORs) and their 95% confidence intervals (CIs). Based on our results, we conducted a systematic literature review using the Medline (OVID) database to identify articles pertaining to the association between family history of melanoma and risk of pancreatic cancer. A meta-analysis including associations in five published studies, unpublished results from a study co-author and the QPCS results was then performed using the DerSimonian and Laird random-effects model. Results: Cases were more likely than controls to report a family history of pancreatic cancer (OR 2.20, 95% CI 1.16–4.19) and melanoma (OR 1.74, 95% CI 1.03–2.95), but not of breast, ovarian, respiratory, other gastrointestinal or prostate cancer. Meta-analysis of melanoma family history and pancreatic cancer risk yielded an OR of 1.22 (95% CI 1.00–1.51). Conclusions: Our results yield further evidence of increased risk of pancreatic cancer in those with family histories of the disease. We also provide suggestive evidence of an association between family history of melanoma and risk of pancreatic cancer.